Experiencing pregnancy in the context of lupus and antiphospholipid syndrome: a grounded theory - Rebeca Rosa de Souza; Mayckel da Silva Barreto; Elen Ferraz Teston; Mariana Torreglosa Ruiz; Erika dos Santos Ratuchnei Dal Pizzol; Mara Cristina Ribeiro Furlan; Maria Aparecida Salci; Sonia Silva Marcon (Universidade Federal do Rio Grande do Sul, 2024)
ABSTRACT Objective: To understand the meanings attributed to pregnancy in the context of Lupus and antiphospholipid syndrome by women and healthcare professionals. Method: Qualitative research, using Symbolic Interactionism as a theoretical framework and Grounded Theory, a constructivist perspective. Data were collected between January and August 2022, through online interviews with 27 women with Lupus located on the social network Facebook and in-person or remote interviews with 12 healthcare professionals. Results: The theoretical model constructed has two categories: "Equal conditions, distinct experiences: experiencing the gestational process" shows that obstetric complications and lack of connection with healthcare professionals trigger negative meanings to the experience; and "Therapeutic management interfering in the attribution of meanings to the experience", demonstrates that the way women interact with healthcare professionals and how they manage treatment favors a positive reframing. Final considerations: The meanings attributed to pregnancy are elaborated and modified according to the interpretation of previous and current experiences, healthcare trajectory and interactions with healthcare professionals. Previous guidance, planning, bonding and trust in healthcare professionals enable positive meanings, while obstetric complications, unqualified assistance and lack of bonding with professionals provide negative meanings.